2015
DOI: 10.1038/jcbfm.2015.93
|View full text |Cite
|
Sign up to set email alerts
|

Cell Tracking Technologies for Acute Ischemic Brain Injury

Abstract: Stem cell therapy has showed considerable potential in the treatment of stroke over the last decade. In order that these therapies may be optimized, the relative benefits of growth factor release, immunomodulation, and direct tissue replacement by therapeutic stem cells are widely under investigation. Fundamental to the progress of this research are effective imaging techniques that enable cell tracking in vivo. Direct analysis of the benefit of cell therapy includes the study of cell migration, localization, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 107 publications
(123 reference statements)
0
22
0
Order By: Relevance
“…9,[21][22][23] Standardized protocols used for labeling stem cells with SPIONs were previously compiled by us, 15,24 and other direct-labeling reagents were reviewed by Marks and Nolan 25 and Progatzky et al 26 Indirect labeling is a considerably different method, which includes genetic modification in order to either produce an appropriate signal-generating molecule or increase the affinity of cells to contrast agents. 9,21,[27][28][29][30][31][32] Transient expression of reporter proteins by DNA vector transfection is often included in this set of cell labeling. 9 Another alternative is stable expression of the reporter protein by transduction of the cells with a virus.…”
Section: Labeling Stem Cells and Molecular Imaging Methodsmentioning
confidence: 99%
“…9,[21][22][23] Standardized protocols used for labeling stem cells with SPIONs were previously compiled by us, 15,24 and other direct-labeling reagents were reviewed by Marks and Nolan 25 and Progatzky et al 26 Indirect labeling is a considerably different method, which includes genetic modification in order to either produce an appropriate signal-generating molecule or increase the affinity of cells to contrast agents. 9,21,[27][28][29][30][31][32] Transient expression of reporter proteins by DNA vector transfection is often included in this set of cell labeling. 9 Another alternative is stable expression of the reporter protein by transduction of the cells with a virus.…”
Section: Labeling Stem Cells and Molecular Imaging Methodsmentioning
confidence: 99%
“…SPECT/CT is one of the most recommended imaging modalities for cell tracking (25,26). We observed that erythropoietin priming of ECFCs increased their ability to home to ischemic tissues and potentiated their beneficial effect on BBB disruption, brain apoptosis, and CBF, as all of these correlated significantly with ECFC homing intensity.…”
Section: Discussionmentioning
confidence: 71%
“…Cell tracking is made feasible through bioluminescent optical imaging at a low cost, however, limited by the low penetration of light. In order to track cells deeper in tissue, positron emission tomography, single-photon emission computed tomography, and magnetic resonance imaging (MRI) can penetrate deeper within a subject utilizing a radioactive isotope (Gavins and Smith, 2015). MRI allows for imaging modalities to assess pathophysiological changes, outcomes of cerebral ischemia, vascular lesions, and blood flow.…”
Section: Perspective and Future Directionsmentioning
confidence: 99%